The social cure : identity, health and well-being - Jetten, Jolanda; Haslam, Catherine; Haslam, S. Alexander (Hove ; New York : Psychology Press, 2012)
(from the cover) A growing body of research shows that social networks and identities have a profound impact on mental and physical health. The challenge we face is explaining why this should be the case. What is it that social groups offer that appears to be just as beneficial as a daily dose of vitamin C or regular exercise? This edited book brings together the latest research on how group memberships, and the social identities associated with them, determine people's health and well-being. The volume provides a variety of perspectives that offer theoretical and empirical insights into these processes and their consequences. The contributions present an analysis of core theoretical issues relating to the ways in which social identities, and factors associated with them (such as social support and a sense of community), can bolster an individual's sense of self and contribute to physical and mental health. It is shown how social identities constitute a "social cure," capable of promoting adjustment, coping and well-being for individuals dealing with a range of illnesses, injuries, trauma, and stressors. In addition, these theories provide a platform for practical strategies that can maintain and enhance well-being, particularly among vulnerable populations. The book presents insights which have implications for health, clinical, social, and organisational psychology and a range of cognate fields. (PsycINFO Database Record (c) 2012 APA, all rights reserved)
(Created by PsycINFO)
List of figures and tables
List of contributors
Preface
Part I: Social identity, health, and well-being
* The case for a social identity analysis of health and well-being / Jolanda Jetten, S. Alexander Haslam, and Catherine Haslam / 3-19
* Group identification, social relationships, and health / Fabio Sani / 21-37
* Promoting positive orientation towards health through social identity / Mark Tarrant, Martin S. Hagger, and Claire V. Farrow / 39-54
* How much is social capital worth? / John F. Helliwell and Christopher P. Barrington-Leigh / 55-71
Part II: Social identity, stigma, and coping
* In sickness and in health: Influences of social categorizations on health-related outcomes / Lindsay St. Claire and Claudine Clucas / 75-95
* Not wanting to grow old: A Social Identity Model of Identity Change (SIMIC) analysis of driving cessation among older adults / Jolanda Jetten and Nancy Pachana / 97-113
* Moving toward or away from a group identity: Different strategies for coping with pervasive discrimination / Nyla R. Branscombe, Saulo Fernandez, Angel Gomez, and Tracey Cronin / 115-131
* Biological and psychosocial responses to discrimination / Kimberly Matheson and Hymie Anisman / 133-153
Part III: Social identity, stress, and trauma
* When other people are heaven, when other people are hell: How social identity determines the nature and impact of social support / S. Alexander Haslam, Stephen D. Reicher, and Mark Levine / 157-174
* Stress and well-being in the workplace: Support for key propositions from the social identity approach / Rolf Van Dick and S. Alexander Haslam / 175-194
* Collective resilience in mass emergencies and disasters: A social identity model / John Drury / 195-215
* Social cure or social curse? The psychological impact of extreme events during the Kosovo conflict / Blerina Kellezi and Stephen Reicher / 217-233
Part IV: Social identity, recovery, and rehabilitation
* Social linkage, self-concept, and well-being after severe traumatic brain injury / Jacinta M. Douglas / 237-254
* Deciding to disclose: The importance of maintaining social relationships for well-being after acquired brain injury / Janelle M. Jones, Jolanda Jetten, S. Alexander Haslam, and W. Huw Williams / 255-271
* The experience of self in the world: The personal and social contexts of identity change after brain injury / Fergus Gracey and Tamara Ownsworth / 273-295
* The importance of remembering and deciding together: Enhancing the health and well-being of older adults in care / Catherine Haslam, Jolanda Jetten, S. Alexander Haslam, and Craig P. Knight / 297-315
Part V: Conclusion
* Advancing the social cure: Implications for theory, practice and policy / Catherine Haslam, Jolanda Jetten, and S. Alexander Haslam / 319-343
Appendix: Measures of identity, health, and well-being
Author index
Subject index
Bibliografija na kraju svakog poglavlja.
Kazalo
Keywords: društvene mreže; grupni identitet; dobrobit -- društveni aspekti; zdravlje -- društveni aspekti